2016
DOI: 10.1002/jsfa.7779
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiles of cow's blood; a review

Abstract: The term 'metabolic profile' refers to the analysis of blood biochemical parameters that are useful to assess and prevent metabolic and nutritional disorders in dairy herds. In the higher standards of milk production, the priority in modern breeding is keeping dairy cows in high lactation and healthy. The proper analysis, as well as control. of their feeding and metabolic status is immensely important for the health condition of the herd. The disproportion between the genetically determined ability for milk pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 82 publications
9
83
2
1
Order By: Relevance
“…The supplements used in our experiments contributed to an increase in the concentration of total cholesterol in the blood plasma of the experimental cows. This situation should be regarded as favorable, since in ruminants, unlike in humans, a reduced concentration of cholesterol may be a problem (43,46). We found that, regardless of the type of supplement used, there was a positive relationship between the duration of application and the content of total cholesterol in blood plasma.…”
Section: Tab 4 Daily Yield Per 100 Days Of Lactationmentioning
confidence: 64%
“…The supplements used in our experiments contributed to an increase in the concentration of total cholesterol in the blood plasma of the experimental cows. This situation should be regarded as favorable, since in ruminants, unlike in humans, a reduced concentration of cholesterol may be a problem (43,46). We found that, regardless of the type of supplement used, there was a positive relationship between the duration of application and the content of total cholesterol in blood plasma.…”
Section: Tab 4 Daily Yield Per 100 Days Of Lactationmentioning
confidence: 64%
“…Accordingly, an increase in blood insulin levels causes a decrease in blood NEFA levels (Brockman, ; Hayirli, ). However, under conditions of energy deficiency, serum NEFA levels increase due to increased induction of adipose tissue mobilization (Grummer, , ; Puppel & Kuczynska, ), and severe energy deficiency can result in disordered lipid metabolism in the liver and increase blood BHB concentrations (Grummer, , ; Puppel & Kuczynska, ). De Koster et al () showed that blood NEFA concentrations reflect energy status rather than IR, although an association did exist between blood NEFA concentrations and IR in over‐conditioned cows; they concluded that RQ, RQ BHB , and HR are not associated with insulin sensitivity as determined by the HEC test in dairy cows at the end of the dry period (De Koster et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Low blood albumin concentrations reflect the progression of fatty liver, and high concentrations indicate hemoconcentration due to dehydration (Kida, ; Puppel & Kuczynska, ). Additionally, leptin is secreted under conditions of adiposity, and low plasma leptin levels are indicative of energy deficiency or fasting (Ahima & Flier, ; Block et al, ; Friedman & Halaas, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the differences in metabolite levels between heifers and cows could be related to fertility differences, it is also possible that they are due to age. Plasma metabolomic profiling has also proven effective at identifying potential biomarkers for metabolic disorders such as ketosis, in dairy cattle 1820 . Furthermore, metabolomic approaches have been extensively used within the biomedical field to develop biomarkers aimed at diagnosing difficult to diagnose pathologies.…”
Section: Introductionmentioning
confidence: 99%